Joint detection of claudin‐1 and junctional adhesion molecule‐A as a therapeutic target in oral epithelial dysplasia and oral squamous cell carcinoma. Issue 10 (3rd June 2019) - Upadhaya, Puja; Barhoi, Dharmeswar; Giri, Anirudha; Bhattacharjee, Abhinandan; Giri, Sarbani
Abstract: Abnormal expression of claudin‐1 (CLDN‐1) and junctional adhesion molecule‐A (JAM‐A) has been described in certain malignancies but their clinical relevance is poorly understood. The present study aims to elucidate the role of CLDN‐1 and JAM‐A in oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC). Changes in the expression of these proteins were identified immunohistochemically on tissue sections from patients with OED and OSCC and compared with control. A correlation between the expression level of proteins and clinicopathological features was analyzed by Pearson's correlation χ 2 test. The survival curve of the follow‐up data was estimated by the Kaplan‐Meier method followed by the log‐rank test. CLDN‐1 and JAM‐A were highly expressed in OED and OSCC tissues when compared to control. Also, delocalization of CLDN‐1 from the membrane to the cytoplasm to the nucleus was observed as the cell proceeds from normal to malignancy. Increased expression of CLDN‐1 and JAM‐A in both OED and OSCC were concomitant with histological grades. In addition, increased JAM‐A was associated with perineural invasion of cancer cells. A positive correlation between the expression level of proteins was observed in OED ( r  = 0.733) and OSCC ( r  = 0.577). Kaplan‐Meier analysis in patients with OSCC showed that the survival rate was lower in patients with high CLDN‐1 and high JAM‐A expression compared to low expressed patients. To conclude, the elevated level and delocalization of CLDN‐1 and JAM‐A suggest their use as tumor markers. A positive correlation between CLDN‐1 and JAM‐A suggests joint detection of these proteins as a future diagnostic tool in oral precancerous and cancerous conditions. Abstract : This study elucidates the expression of claudin‐1 (CLDN‐1) and junctional adhesion molecule‐A (JAM‐A) in oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC). Overexpression of CLDN‐1 and JAM‐A in both OED and OSCC were concomitant with aggressive histological grades. We report a positive correlation between CLDN‐1 and JAM‐A for the first time in OED and OSCC tissues suggesting joint detection of these proteins as a future diagnostic tool in oral precancerous and cancerous conditions.